Analisis Proses dan Hambatan Pendaftaran Motif Tenun Suat Songket Baduy Luar sebagai Indikasi Geografis Asal Provinsi Banten - Sofiyatul Syafira; Sepriyadi Adhan; Moh. Wendy Trijaya (Lembaga Yasin AlSys, 2025)
This study is motivated by the existence of Tenun Baduy Luar from Desa Kanekes, Banten Province, as an important cultural heritage that embodies the aesthetic, philosophical, and cultural identity values of the Baduy community. Produced using traditional techniques with the unique and highly meaningful Suat Songket motif, this weaving reflects the community’s close relationship with nature and customary traditions, yet it has not obtained legal protection as Indikasi Geografis (Geographical Indication, GI) in accordance with Undang-Undang Nomor 20 Tahun 2016. The research aims to identify and analyze the obstacles in the process of recognizing the Suat Songket weaving motif as a GI originating from Banten Province, examined from legal, administrative, and sociocultural aspects, as well as from the level of awareness among indigenous communities regarding the protection of communal intellectual property. The study employs an empirical juridical approach, using primary data collected through interviews with artisans, customary leaders, and relevant local government officials, and secondary data obtained through literature review; legal and sociological approaches are applied to examine regulations and the socio-cultural conditions of the Baduy community. The findings show that the Suat Songket motif possesses distinctive characteristics closely linked to the geographical and cultural identity of the Baduy people, but it has not yet fully met the requirements for legal protection under the GI scheme. The main obstacles include the absence of a formally structured managing organization, limited integration of administrative data among local stakeholders, and insufficient outreach on the importance of GI for the preservation and protection of communal intellectual property. The study concludes that GI recognition for the Suat Songket weaving motif has the potential to provide effective legal protection, safeguard product authenticity and quality, and enhance its economic value and competitiveness in both local and global markets. The implications highlight the importance of government support and active participation of indigenous communities as key to realizing the sustainable preservation and development of weaving crafts based on Geographical Indications.